SISTER EVA MICHALAK, AT THE AGE OF NINETY FOUR, A RESEARCHER AND SELF TAUGHT THAT WITH HER WISDOM GATHERED ONE OF THE LARGER COLLECTIONS OF MEDICINAL AND FRUITBEARING PLANTS OF THE SANTA CATARINA STATE - Souza, Barcelos de (Revista de Ciências Agroveterinárias, 2006)
Entrevista com Irmã Eva Michalak.